Modern trends in medicine: from microbiome to systemic complications - A. D. Makatsariya; A. V. Vorobev (Акушерство, гинекология и репродукция, 2025)
The articles in this issue cover a wide range of topics, including the role of the maternal microbiome in fetal growth restriction, the effectiveness of therapy for mixed vaginitis, management strategies for pregnant women with COVID-19, the impact of environmental factors on reproductive health, thrombotic complications of chemotherapy, the connection between the microbiome and obesity, as well as rare clinical cases. Innovations in diagnostics, treatment, and screening are explored, from non-invasive prenatal testing to mathematical models for studying autism. The articles emphasize the importance of a comprehensive approach and the integration of modern technologies.